The Intersection of Entertainment and Commerce: Buzzohero’s TikTok Strategy in Social Commerce - Hannidah Islahiyah; Gebby Septia Akhdev Pratiwi; Nabila Sekar Arum Hasanah (Journal of Communication and Public Relations, 2025)
Digital marketing is developing more and more significantly, especially since the Covid-19 pandemic in 2020. The decision to stay at home in several countries including Indonesia has forced various levels of society to work from home. As a result, many individuals use social media to carry out activities such as seeking entertainment, socializing, and shopping for daily necessities. This change in behaviour brings fresh air to the Indonesian advertising industry. The use of social media for commercial, entertainment and social purposes has become a new phenomenon called social media commerce. Buzzohero as a Social Media Advertising Platform takes this opportunity by optimizing the TikTok Live Streaming feature in marketing products from various brands, which are their clients. This study aims to analyse Buzzohero's strategy in forming engagement through Social Commerce on TikTok Live Streaming. This study uses a qualitative methodology with an interpretive paradigm. The data collection technique uses interviews as primary data. While the secondary data the authors obtained through observations on TikTok Live Streaming content, documentation, and literature. The results of this research analysis associated using the RACE model (Reach, Act, Convert, and Engage) as a digital marketing framework representing distinct stages of the marketing process that is widely used that facilitates the development and implementation of successful marketing strategies.